2020
DOI: 10.3390/su12229472
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety System (HACCP) as Quality Checkpoints in a Spin-Off Small-Scale Yogurt Processing Plant

Abstract: The present study describes the implementation of a food safety system in the dairy pilot plant “Gourmeticus Academicum,” a spin-off within the University of Agricultural Sciences and Veterinary Medicine of Cluj Napoca, Romania. In order to improve Hazard Analysis of Critical Control Points (HACCP) the preliminary programs were integrated into the quality management system (QMS) by monitoring the biological hazards. The process provides future specialists with good practice hands-on and educational tools. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Studies have indicated that HACCP implementation requires the support of a robust PRP, which represents the basic conditions and activities that are necessary to maintain a hygienic environment throughout the entire food supply chain. Such conditions and activities are suitable for each phase in the production, handling, and provision of end products in the form of food safe for human consumption (Gaaloul, Riabi, & Ghorbel, 2011; Mureşan et al, 2020; Trafialek & Kolanowski, 2017). Prior to HACCP and ISO 22000:2018 implementation, the organization in this study took into account various factors such as: high‐quality or verified raw materials; competence of the food safety team; personnel hygiene and buildings; equipment and workplace sanitation; equipment maintenance and repair; and compliance with GHP Good Agricultural Practices (GAP), Good Manufacturing Practice (GMP), Good Production Practice (GPP), Good Distribution Practice (GDP), etc .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that HACCP implementation requires the support of a robust PRP, which represents the basic conditions and activities that are necessary to maintain a hygienic environment throughout the entire food supply chain. Such conditions and activities are suitable for each phase in the production, handling, and provision of end products in the form of food safe for human consumption (Gaaloul, Riabi, & Ghorbel, 2011; Mureşan et al, 2020; Trafialek & Kolanowski, 2017). Prior to HACCP and ISO 22000:2018 implementation, the organization in this study took into account various factors such as: high‐quality or verified raw materials; competence of the food safety team; personnel hygiene and buildings; equipment and workplace sanitation; equipment maintenance and repair; and compliance with GHP Good Agricultural Practices (GAP), Good Manufacturing Practice (GMP), Good Production Practice (GPP), Good Distribution Practice (GDP), etc .…”
Section: Resultsmentioning
confidence: 99%
“…These systems help to ensure that food products are safe and of high quality. It is stated that the implementation of Hazard Analysis and Critical Control Points (HACCP) in small-scale food processing facilities can help to improve the safety and quality of food products [ 39 ]. Also, the use of microbiological testing to ensure the safety and quality of food products is an important component of many quality management systems [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the hazard nature biological or chemical, the probability of occurrence and severity level is done (Table 2), and then the rating of hazard is calculated [4].…”
Section: Identification Of the Hazardsmentioning
confidence: 99%
“…Principle 7 Establish documentation and record-keeping HACCP 1 , CCPs. 2 according to Mureşan et al [4]. manufacturing process, samples were taken and collected for analysis from 10 lots, before and after HACCP applying, from raw materials such as; raw milk, salt, and rennet enzyme, additionally water supply, samples were taken throughout the ten lots of production (10 samples for each).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation